Multimodality treatment in recurrent/metastatic squamous cell carcinoma of head and neck: current therapy, challenges, and future perspectives - Pannunzio, Sergio; Di Bello, Armando; Occhipinti, Denis; Scala, Alessandro; Messina, Gloria; Valente, Giustina; Quirino, Michela; Di Salvatore, Mariantonietta; Tortora, Giampaolo; Cassano, Alessandra (Frontiers in Oncology, 2024)
With this review we want to highlight the main treatments, difficulties, uncertainties, and future challenges in the management of the recurrent/metastatic head and neck squamous cell carcinoma. This disease is extremely complex and heterogeneous, and treatment often needs to be tailored to the individual patient and based on the disease characteristics. In most cases, these patients are frail requiring a multidisciplinary approach to identify the correct frame within which attributing the best setting for each patient. Treatment is changing rapidly, and new approaches are being explored, creating new challenges for the physicians and opportunities for the patients.